A cloudy conundrum. - Chua, Tin Giap. (2010)
A detailed report on the working process, problems encountered, and thinking process that led to the completion of the animated short A Cloudy Conundrum. Our project is a short film that last about 5minutes long, filled with gags, tensions, secrets and surprises.